Guillermo Gómez-Peña’s performance praxis as decolonial public pedagogy: deconstructing borders, redefining identities, and decolonizing the gaze - Balán, Laura (Frontiers in Communication, 2025)
This article clarifies and emphasizes Guillermo Gómez-Peña and La Pocha Nostra’s long-standing articulation of performance as decolonial pedagogy, foregrounding their praxis not merely as activism or artistic provocation but as a sustained, embodied, and public form of decolonial education. The analysis highlights how Gómez-Peña’s own publications—including Exercises for Rebel Artists (2011) and La Pocha Nostra: A Handbook for the Rebel Artist (2021)—articulate the work as decolonial in essence, though its pedagogical dimensions have often remained underexamined in scholarship. Drawing on postcolonial theory (Bhabha, Said, Spivak), borderlands scholarship (Anzaldúa), performance studies (Schechner, Taylor), critical pedagogy (Freire, Giroux, Hooks), and visuality/colonial optics (Mirzoeff, Rancière), as well as recent dialogues in Global Performance Studies (2022) on decolonization and performance, the article situates Gómez-Peña’s hybrid personae, border praxis, and audience-engaged strategies as practices of radical citizenship that teach through disruption, disorientation, and imaginative intervention. His performances collapse the spectator/performer binary, mobilize linguistic and cultural hybridity as epistemic tools, and interrogate the colonial gaze by reworking the conditions of visibility and authenticity. The study argues that his work operates as public pedagogy, creating civic spaces where knowledge production, identity negotiation, and anti-colonial consciousness coalesce in performative encounter, illuminating the pedagogical intentionality that has always been central to La Pocha Nostra’s ethos.